Osteoporosis and Low Bone Mineral Density in Men with Testosterone Deficiency Syndrome. Issue 4 (30th July 2015) - Gaffney, Christopher D.; Pagano, Matthew J.; Kuker, Adriana P.; Stember, Doron S.; Stahl, Peter J.
Abstract Introduction Testosterone deficiency syndrome (TDS) is a risk factor for low bone mineral density (BMD) and osteoporosis. Knowledge of the relationship between TDS and bone health, as well as the practical aspects of how to diagnose and treat low BMD, is therefore of practical importance to sexual medicine practitioners. Aim The aim of this study was to review the physiologic basis and clinical evidence of the relationship between TDS and bone health; and to provide a practical, evidence‐based algorithm for the diagnosis and management of low BMD in men with TDS. Methods Method used was a review of relevant publications in PubMed. Main Outcome Measures Pathophysiology of low BMD in TDS, morbidity, and mortality of osteoporosis in men, association between TDS and osteoporosis, indications for dual X‐ray absorptiometry (DXA) scanning in TDS, evidence for testosterone replacement therapy (TRT) in men with osteoporosis, treatment for osteoporosis in the setting of TDS. Results Sex hormones play a pleomorphic role in maintenance of BMD. TDS is associated with increased risk of osteoporosis and osteopenia, both of which contribute to morbidity and mortality in men. DXA scanning is indicated in men older than 50 years with TDS, and in younger men with longstanding TDS. Men with TDS and osteoporosis should be treated with anti‐osteoporotic agents and TRT should be highly considered. Men with osteopenia should be stratified by fracture risk. Those at high risk should be treated with anti‐osteoporotic agents with strong consideration of TRT; while those at low risk should be strongly considered for TRT, which has a beneficial effect on BMD. Conclusion Low BMD is a prevalent and treatable cause of morbidity and mortality in men with TDS. Utilization of a practical, evidence‐based approach to diagnosis and treatment of low BMD in men with TDS enables sexual medicine practitioners to make a meaningful impact on patient quality of life and longevity. Gaffney CD, Pagano MJ, Kuker AP, Stember DS, and Stahl PJ. Osteoporosis and low bone mineral density in men with testosterone deficiency syndrome. Sex Med Rev 2015;3:298–315.